List-Chromatic Number and Chromatically Unique of the Graph Kr2 + Ok - Xuan Hung, Le (2019)
In this paper, we determine list-chromatic number and characterize chromatically unique of the graph G = Kr2 +Ok. We shall prove that ch(G) = r + 1 if 1<=k<=2, G is x-unique if 1<=k<=3.